PENGARUH SUHU DAN LAMA PENYIMPANAN TERHADAP KANDUNGAN VITAMIN A DAN VITAMIN C BUAH GANDARIA (Bouea macrophylla Griff) SERTA IMPLIKASINYA PADA PEMBELAJARAN BIOLOGI - Agnes A Patty; Pamela Papilaya; Prelly Tuapattinaya (Program Studi Pendidikan Biologi FKIP Unpatti, 2016)
Background: The purpose of this study was to determine whether there is influence of temperature and storage time to vitamin A and vitamin C content in gandaria. Method: This study was an experimental study using Completely Randomized Design (RAL), with a combination of cold and room temperature treatments and storage duration (1, 4, 7, and 10 days). Each treatment was repeated three times. The parameters observed were vitamin A and vitamin C content of gandaria. Analysis of vitamin A and C content using UV-Vis Spectrophotometric method. The data obtained were analyzed with ANOVA and continued with Duncan Test. Results: The results showed that temperature and storage time had an effect on vitamin A and vitamin C content of gandaria. The highest decrease in vitamin A content was found in storage at room temperature for 10 days that was 21.69%, while in cold temperature only 15.36%. The content of vitamin C in gandaria stored at room temperature for 10 days decreased 35.05%, while in cold temperature only 21.03%. Conclusion: The longer the storage and the high temperature, the levels of vitamin A and vitamin C decreases.